Genetic nephrotic syndrome associated with disturbed function of glomerular slit membrane and podocyte cytoskeleton in children - Pitekova, Barbora; Bezdicka, Martin; Konopasek, Patrik; Breza, Jan; Bartoň, Peter; Zieg, Jakub (Clinical and experimental nephrology, 2023)
BACKGROUND: Genetic nephrotic syndrome is caused by pathogenic variants in genes encoding proteins necessary for the stability and functionality of the glomerular filtration barrier. To date, more than 70 genes associated with steroid-resistant nephrotic syndrome have been identified. We review the clinical and molecular aspects of genetic nephrotic syndrome with a particular focus on genes associated with slit membrane and podocyte cytoskeleton defects. Sanger sequencing and next-generation sequencing are widely used in the identification of novel gene variants and help us gain a better understanding of the disease. Despite these findings, therapy is mainly supportive and focused on the reduction of proteinuria and management of chronic kidney disease with an unfavorable outcome for a significant proportion of cases. Positive therapeutic effects of immunosuppressive drugs have been reported in some patients; however, their long-time administration cannot be generally recommended. CONCLUSION: Personalized treatment based on understanding the distinct disease pathogenesis is needed. With this, it will be possible to avoid harmful immunosuppressive therapy and improve outcomes and quality of life for pediatric patients suffering from genetic nephrotic syndrome.
Keywords: nemoci ledvin; Nephrotic Syndrome; Kidney Diseases; Cytoskeleton; glomerulus; cytoskelet; kvalita života; Child; lidé; Kidney Glomerulus; dítě; Podocytes; Quality of Life; nefrotický syndrom; podocyty; Humans